Laparoscopic Splenectomy in Children: A Modified Technique with Joint Sealing of Segmental Splenic Arteries and Veins Favorably Compared with the Classic Technique - Silvaroli, Sara; Montalembert, Marianne De; Sauvat, Frédérique; Brousse, Valentine; Sarnacki, Sabine; Irtan, Sabine (European Journal of Pediatric Surgery, 2017)
Introduction Splenectomy in children is nowadays widely performed by laparoscopy, the major risk being operative hemorrhage. We hereby compare the results of two different techniques of vascular control.Materials and Methods We retrospectively reviewed all patients undergoing a laparoscopic splenectomy (LS) for hematologic disease at a single institution from 2004 to 2013. LS was performed by a lateral approach. The 10-mm optic port was placed in the umbilicus and two 5-mm working ports were placed in the left lower quadrant and in the right upper quadrant near the midline.An additional port was added in the epigastrium if needed. The classic technique (CT) consisted in the separate sealing and section of the splenic artery and vein above the pancreas tail. The modified technique (MT) consisted in the dissection of each segmental splenic vessel, at the lower, middle, and upper parts of the spleen. They were then divided without individualizing the artery from the vein.Results Total 69 patients were operated on at a mean age of 7.8 ± 0.6 years, 30 by CT and 39 by MT. In 20 patients (6 CT, 14 MT) a cholecystectomy was associated. The operative time, length of hospitalization, and number of postoperative complications for CT/MT were respectively 139/117 mn (p = 0.04), 3.8/3.0 days (p = 0.01), 12/3 (p = 0.002). An additional port was less needed with MT (p = 0.03).Conclusions The joint sealing of segmental splenic artery and vein appeared safe, efficient and quicker for LS, with no increased risk of operative bleeding and postoperative complications.
Keywords: laparoscopy; splenectomy; children